USE OF CONJOINT REACTIONS FOR EXTRACTION OF METALS FROM MINERAL RAW MATERIALS - B.B. Kenzhaliev; А.N. Berkinbayeva; E.N. Suleimenov (European Scientific Journal, ESJ, 2014)
In the article there are some data on extraction of metals into a solution from compound mineral raw materials by means of electrochemical leaching. Leaching reagent (sodium thiosulfate, etc.) was obtained at the same time with reaction of resolving metals in a solution of sodium alkali. Resource of sulfur for obtaining the leaching reagent was a composite sulfurgraphite electrode, which was used at metal resolution as a cathode and as an anode. At that there were obtained similar results on extraction of metals into a solution.